The Effectiveness of the Work of Government Employees with Employment Agreement (AGEEA) in an Increase Public Service on the Secretariat District of South Manokwari, West Papua Province - Welfris Diego Armando (Institut Pemerintahan Dalam Negeri (IPDN), 2018)
Acceptance Government Employees with Employment Agreement (AGEEA) or labor of honorary in the scope of local government in South of Manokwari, is because of lack of Apparatus Civil State (ACS), but admissions process is not through phases test competency or through Analysis of the Needs of Employees so the labor of honorary who received has a very low ability, but because so many labors of honorary, district government in South of Manokwari must spend a very large cost to finance the labor of honorary. However, in terms of public service, still considered need to be improved. Therefore the author interested to investigate the research entitled